The Importance and Limitations of Participation in Development Projects and Programmes - Mubita, Aurick; Libati, Mundia; Mulonda, Munalula (European Scientific Journal, ESJ, 2017)
This paper discusses the importance and limitations of participation of local people in development projects and programmes while making suggestions on how to enhance such participation. The paper reveals that participation resulted from the paradigm shift that emerged from the failure of ‘top-down approaches’ or growth models of development. It also arose due to development actors’ realization that approaches to development needed to be adapted to local conditions that are shaped by different sociocultural, economical and political realities. The paper adopts a desk review, conceptual analysis of the importance and limitations of participation of local people in development projects and programmes, placing particular focus on two 1994 publications by Robert Chambers, as key sources of literature on the origins of participation. Using Sherry Arnstein’s understanding of participation where she equates it with the concept of power, participation can enhance empowerment of the locals and can provide local people with the opportunity to think and develop solutions for themselves. Participation can also allow the incorporation of local knowledge, skills and resources in the design of interventions, it can ensure project/programme responsiveness to people’s needs, it can enhance the goal of sustainability and assist breaking the mentality of dependency. Critics assert that participation does not lead to locals’empowerment, because participatory methodologies fail to change and challenge the bureaucratic, centralized and administrative structures that control decision-making and resource allocation. Also, through participation, what could be considered to be local knowledge might just be a construction of the planning context that cover a complex micropolitics of knowledge production and use in local communities. Domination also limit participation since participatory activities take place in groups. Particiaptory techniques conceal traditional local relationships of power and fail to deal with situations where local culture hinders participation by being oppressive to certain people. Therefore, participation is affected by spatial, temporal, political, social and cultural contexts. Thus, to ensure successful participation, there is need to contextualize it within the existing local environment. It is important to situate efforts whose aim is to engage communities in context if they are to be successful. This is because contexts in which different development organizations and agencies operate are complex and diverse. Participation must be informed by carefully done political and social analyses. By so doing, an examination of the practices and social relationships that determine local knowledge production and use can be made. Participation should be considered as political as it is conditioned by the institutional framework and political backgrounds of the participants.